THE ROLE OF NATIONAL VALUES AND FAMILY IN EDUCATING YOUNG PEOPLE AS HIGHLY SPIRITUAL PEOPLE - Temirov Sheroz Turayevich (Galaxy International Interdisciplinary Research Journal, 2022)
The development of the young generation into selfless and perfect people for the country is analyzed from a spiritual and moral point of view. The article describes the interpretation of perfection, the role of educational and spiritual importance in the formation of a perfect person in society today, birth and death, joy and sorrow, dreams and aspirations are manifested in human life.